On a new tribe, genus and species of Cypricercinae McKenzie, 1971 (Crustacea, Ostracoda, Cyprididae) from New Caledonia (Pacific Ocean) - Martens, Koen; Almeida, Nadiny Martins De; Páll-Gergely, Barna; Higuti, Janet (Zootaxa, 2023)
The New Caledonian Archipelago is a hot spot for biodiversity and endemism. Here, we describe Lithocypris peyia gen. et spec. nov. Martens, Almeida & Higuti from a single locality (a lithotelma, or rockpool) on “Grande Terre”, the main island of the archipelago. The new genus belongs to the subfamily Cypricercinae and to the new tribe Lithocypridini trib. nov. based on the absence of a groove and anterior inner lists in the left valve, on several aspects of the chaetotaxy, of the prehensile palps and of the hemipenis, and on the fact that the Triebel’s Loop is situated in the dorsal branch of the attachment of the caudal ramus. Lithocypris gen. nov. can further be distinguished from the other genera in the subfamily by a combination of features: carapace elongated in lateral view and narrow in dorsal view, left valve with a weak ventral and posterior inner list only, antennule with both Wouters and Rome organs, maxillula with elongated and rectangular second palp segment and very short sideways directed bristles, first thoracopod with setae a, b and d present and with female palp short and plump, second thoracopod with setae d1 and d2 very short, third thoracopod with seta f missing and Zenker organ with a crown.